Advances in the mechanisms and applications of inhibitory oligodeoxynucleotides against immune-mediated inflammatory diseases - Wang, Hongrui; Su, Yingying; Chen, Duoduo; Li, Qi; Shi, Shuyou; Huang, Xin; Fang, Mingli; Yang, Ming (Frontiers in Pharmacology, 2023)
Inhibitory oligodeoxynucleotides (ODNs) are short single-stranded DNA, which capable of folding into complex structures, enabling them to bind to a large variety of targets. With appropriate modifications, the inhibitory ODNs exhibited many features of long half-life time, simple production, low toxicity and immunogenicity. In recent years, inhibitory ODNs have received considerable attention for their potential therapeutic applications in immune-mediated inflammatory diseases (IMIDs). Inhibitory ODNs could be divided into three categories according to its mechanisms and targets, including antisense ODNs (AS-ODNs), DNA aptamers and immunosuppressive ODNs (iSup ODNs). As a synthetic tool with immunomodulatory activity, it can target RNAs or proteins in a specific way, resulting in the reduction, increase or recovery of protein expression, and then regulate the state of immune activation. More importantly, inhibitory ODNs have been used to treat IMIDs, including inflammatory disorders and autoimmune diseases. Several inhibitory ODN drugs have been developed and approved on the market already. These drugs vary in their chemical structures, action mechanisms and cellular targets, but all of them could be capable of inhibiting excessive inflammatory responses. This review summarized their chemical modifications, action mechanisms and applications of the three kinds of inhibitory ODNs in the precise treatment of IMIDs.